THE AEVIT DRUG EFFECT - Axmedov Shamshod Jamshidovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. In children with perinatal pathology of central nervous system content of vitamins A and E was decreased in blood serum. At the same time, some patterns of lipid and protein metabolism were altered. These alterations were especially distinct in pathological conditions accompanied by inflammatory reaction due to infections. Parenteral administration of a complex of vitamins A and E (drug "Aevit") within 2 weeks led to normalization of the content of these vitamins in blood serum. At the same time, the altered patterns of lipid and protein metabolism were normalized.